2019
DOI: 10.1063/1.5117887
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Janus disks confined in a slit

Abstract: Using Monte Carlo simulations, we investigate the self-organization of Janus disks confined in two-dimensional slits. Janus particles are modeled as circles composed of attractive and repulsive parts. We consider the slits with identical walls and slits with competing walls (the so-called Janus-like pores). We investigate how the system morphology depends on the slit width, density, and temperature. Different unique orientationally ordered structures are found. The mechanism of formation of these structures is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Another interesting class of systems with strongly orientational interactions consists of colloidal patchy particles [ 34 , 35 , 36 ] A special case of patchy particles, corresponds to Janus particles, in which there are only two regions of different chemical composition and physical properties [ 35 ]. Self-assembly of Janus particles has been studied experimentally [ 34 , 37 , 38 ] and with different theoretical tools [ 39 , 40 ], including computer simulations [ 41 , 42 , 43 ]. Adsorption of Janus particles at the fluid-fluid interface has been theoretically studied by several authors [ 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting class of systems with strongly orientational interactions consists of colloidal patchy particles [ 34 , 35 , 36 ] A special case of patchy particles, corresponds to Janus particles, in which there are only two regions of different chemical composition and physical properties [ 35 ]. Self-assembly of Janus particles has been studied experimentally [ 34 , 37 , 38 ] and with different theoretical tools [ 39 , 40 ], including computer simulations [ 41 , 42 , 43 ]. Adsorption of Janus particles at the fluid-fluid interface has been theoretically studied by several authors [ 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…We consider spherical Janus particles between two planar surfaces located at a distance of L. Each Janus particle (JP) consists of two hemispheres, A and R, and the A (R) parts are attractive (repulsive). The total pair potential between two Janus particles is expressed as a sum of the hard sphere potential, v JJ hs , and the anisotropic contribution 8,32…”
Section: ■ Methodsmentioning
confidence: 99%
“…The behavior of amphiphilic JPs in two-dimensional slits has been explored using Monte Carlo simulations. 32 Slits with identical walls and Janus-like slits have been considered. The study has shown that interactions between particles, the nature of "walls", and their separation strongly affect the self-assembly.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations